2015
DOI: 10.1371/journal.pone.0132726
|View full text |Cite
|
Sign up to set email alerts
|

Evidence from Meta-Analyses of the Facial Width-to-Height Ratio as an Evolved Cue of Threat

Abstract: The facial width-to-height ratio (FWHR) is the width of the face divided by the height of the upper face. There is mixed evidence for the hypothesis that the FWHR is a cue of threat and dominance in the human face. We conducted a systematic review and meta-analyses of all peer-reviewed studies (and 2 unpublished studies) to estimate the magnitude of the sex difference in the FWHR, and the magnitude of the relationship between the FWHR and threatening and dominant behaviours and perceptions. Studies were eligib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
254
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 214 publications
(271 citation statements)
references
References 77 publications
14
254
3
Order By: Relevance
“…For males, we don't find a relation between fWHR and rejection, despite the fact that fWHR has been associated with threat behavior for men and not for women (Geniole et al 2015). …”
Section: Do Observers Use Cues Associated With Rejections?contrasting
confidence: 65%
See 1 more Smart Citation
“…For males, we don't find a relation between fWHR and rejection, despite the fact that fWHR has been associated with threat behavior for men and not for women (Geniole et al 2015). …”
Section: Do Observers Use Cues Associated With Rejections?contrasting
confidence: 65%
“…The facial measures we use are (1) facial width-to-height ratio (fWHR), (2) facial masculinity (fM), (3) and facial asymmetry (fA). In human males, a small but significant relationship exists between fWHR and aggressive tendencies (see Geniole et al, 2015;Haselhuhn, Ormison and Wong, 2015 for meta-studies).…”
Section: Facial Measuresmentioning
confidence: 99%
“…In the current work, we focused on fWHR as a facial stereotype, demonstrating the relationship between fWHR and how targets are perceived. Past work has found that individuals with relatively higher fWHR are perceived as threatening, dominant, and angry (e.g., Geniole et al, 2015). suggests that they should be the most deserving of protection.…”
Section: Discussionmentioning
confidence: 99%
“…However, in addition to the possibility that we were simply unable to detect effects of fWHR due to sample size, the results of a recent meta-analysis showed that BMI and fWHR are positively significantly correlated (Geniole et al 2015), suggesting that fWHR may still have an important association with formidability in women. Indeed, Lefevre et al (2014) showed that women's selfreported verbal aggression was positively related to fWHR.…”
Section: Discussionmentioning
confidence: 95%
“…Although the results of a recent meta-analaysis showed a positive association between fWHR and BMI in women (Geniole et al 2015), a relative lack of data from studies investigating the relationship between these variables and women's threat and dominance behavior precludes the conclusion that either is an exclusive indicator of their formidability. In order to determine whether fWHR or body size provides a more accurate indication of formidability in women, we investigated whether fWHR and BMI were significant predictors of fighting ability in professional female fighters.…”
Section: Introductionmentioning
confidence: 98%